PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI MANFAAT, DAN PERSEPSI KEPERCAYAAN TERHADAP MINAT PENGGUNAAN QRIS SEBAGAI ALAT TRANSAKSI PEMBAYARAN DIGITAL DI KOTA PEKANBARU - Khairani, Radha; Hichmaed Tachta Hinggo; Fitri Ayu Nofirda (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of this study is to determine the influence of perceived ease of use, perceived usefulness, and perceived trust on the intention to use QRIS as a digital transaction tool in Pekanbaru City. This research employs a quantitative approach with a sampling technique based on Hair's formula, involving 160 respondents. Data were collected through the distribution of questionnaires, using both primary and secondary data sources. The study applies descriptive statistical analysis, respondent response analysis, validity testing, reliability testing, normality testing, heteroscedasticity testing, multicollinearity testing, multiple linear regression analysis, t-tests, and determination coefficient analysis, processed using SPSS version 26. The results indicate that the perceived ease of use (X1) and perceived usefulness (X2) variables have a positive and significant influence on the intention to use (Y). Conversely, the perceived trust variable (X3) has a positive but not significant influence on the intention to use (Y).